Evaluating the effectiveness of Literacy and Numeracy Programs Using Educational Report Analysis: A Case Study at SD Sumbermulyo - Ari Pujiningsih; Ngurah Ayu Nyoman; Muhammad Prayito (FKIP - Universitas Riau, 2026)
Literacy and numeracy are essential foundational competencies, yet many primary schools continue to face challenges in meeting expected mastery levels. SD Sumbermulyo in Sarang District, Rembang Regency implements literacy and numeracy programs aligned with the Merdeka Curriculum; however, educational report data show significant gaps in student achievement. This study aims to evaluate the effectiveness of these programs by analyzing their planning, implementation, and control, as well as students’ competency outcomes. Using a qualitative approach, data were collected through interviews with school stakeholders, classroom observations, and analysis of educational reports. The findings reveal that although the school has organized structured programs supported by teacher involvement and basic learning resources, more than 60% of students especially in lower grades have not met minimum reading and arithmetic standards. The study concludes that improving program effectiveness requires data-based adjustments, enhanced learning materials, improved time allocation for literacy activities, and stronger collaboration among teachers, parents, and the community. Overall, this research highlights the importance of educational report analysis as a practical tool for evaluating and strengthening literacy and numeracy programs in primary schools.